Elucidation of near-resonance vibronic coherence lifetimes by nonadiabatic electronic-vibrational state character mixing - Yeh, Shu-Hao (Proc Natl Acad Sci U S A, 2019)
Recent work suggests that the long-lived coherences observed in both natural and artificial light-harvesting systems (such as the Fenna–Matthews–Olson complex) could be attributed to the mixing of the pigments’ electronic and vibrational degrees of freedom. To investigate the underlying mechanism of these long coherence lifetimes, a sophisticated description of interactions between the molecular aggregates and the nonequilibrium fluctuations in the surrounding environment is necessary. This is done by implementing the hierarchical equations of motion approach on model homodimers, a method used in the intermediate coupling regime for many molecular aggregates wherein the nonequilibrium environment phonons play nontrivial roles in exciton dynamics. Here we report a character change in the vibronic states—reflective of property mixing between the electronic and vibrational states—induced by an interplay between system coupling parameters within the exciton-vibrational near-resonance regime. This mixing dictates vital aspects of coherence lifetime; by tracking the degree of mixing, we are able to elucidate the relationship between coherence lifetime and both the electronic energy fluctuation and the vibrational relaxation dephasing pathways.